Heterokaryotic state of a point mutation (H249Y) in SDHB protein drives the evolution of thifluzamide resistance in Rhizoctonia solani. Issue 3 (16th November 2020) - Miao, Jianqiang; Mu, Wenjun; Bi, Yang; Zhang, Yanling; Zhang, Shaoliang; Song, Jizhen; Liu, Xili
Abstract: BACKGROUND: Sheath blight, caused by Rhizoctonia solani, can be effectively controlled by application of the succinate dehydrogenase inhibitor thifluzamide. Although the risk of resistance to thifluzamide in R. solani had been reported, the thifluzamide‐resistance mechanism and the evolution of thifluzamide‐resistance in R. solani have not been investigated in detail. RESULTS: No differences were found between the sequences of proteins SDHA, SDHC, and SDHD in thifluzamide‐sensitive isolates and thifluzamide‐resistant mutants, but a single point mutation H249Y was found in SDHB. Two different types of thifluzamide‐resistant R. solani mutants were characterized: homokaryotic, carrying only the resistance allele; and heterokaryotic, retaining the wild‐type allele in addition to the resistance allele. The resistance level differed according to the nuclear composition at codon 249 in the sdhB gene. Molecular docking results suggested that the point mutation (H249Y) might significantly alter the affinity of thifluzamide and SDHB protein. Heterokaryotic mutants were able to evolve into a homokaryon when repeatedly cultured on agar media or rice plants in the presence of thifluzamide, but thifluzamide treatment had no effect on the genotypes of homokaryotic mutants or sensitive isolates. CONCLUSION: This study showed that H249Y in SDHB protein could cause thifluzamide resistance in R. solani . Fungicide application could promote heterokaryotic mutants to evolve into a homokaryon. © 2020 Society of Chemical Industry Abstract : H249Y in SDHB protein could cause thifluzamide resistance in Rhizoctonia solani . Fungicide application could promote heterokaryotic mutants to evolve into a homokaryon.